Inter-Regional Spillovers and Urban-Rural Disparity in U.S. Employment Growth - Hisamitsu Saito; Munisamy Gopinath; Junjie Wu (European Regional Science Association (ERSA), 2010)
A wide urban-rural disparity is observed in employment growth in the United States. For example, employment growth averaged 2.1 percent in urban counties during 1998-2007, compared with just 1 percent in rural counties. In this study, we examine the sources of U.S. employment growth using the county-level industry data. From an analytical labor-market model, we derive equilibrium employment growth as a function of growth in neighborhood characteristics and initial conditions such as accumulated of human capital, industrial structure and natural amenities. The equilibrium employment growth equation is then estimated using spatial econometric techniques, which account for spillovers from employment growth in neighboring counties. Specifically, a spatial lag model is estimated using U.S. county and industry data from 1998-2007. Results show positive growth spillovers from both urban and rural regions, but the former has relatively large impacts on regional employment growth. The statistical significance of the spatial-lag coefficient in most U.S. manufacturing and service industries suggests the presence of a strong spatial multiplier effect. Evaluating the contribution of alternative factors to employment growth, we find that initial accumulated human capital is the key determinant of regional employment growth. The decomposition of the urban-rural gap in employment growth shows spillovers from urban (rural) regions widen (narrow) the gap. The latter suggests that collaboration among rural regions in economic development can be effective in narrowing the urban-rural gap in employment growth.
Keywords: R11; J21; C21; 330; Employment growth; Spatial econometrics; Spillovers